PENGARUH PERPUTARAN KAS DAN LIKUIDITAS (CURRENT RATIO) TERHADAP PROFITABILITAS (RETURN ON ASSET) - M Muslih (Faculty of Economics and Business, Universitas Warmadewa, 2019)
This research aims is to determine the Effect of Cash and Liquidity Turnover (Current Ratio) on Profitability (Return On Assets) on companies listed on the Indonesia Stock Exchange opposite 7 Companies. Sampling in this research is uses purposive sampling technique. Sample samples of 7 companies and observations were carried out for 5 years, namely 2012,2013,2014,2015, and 2016. Data collected methods is using documentation techniques. The analysis techniques that are classic assumption test, multiple linear regression, f-test t-test, and determinant coefficient. The processing data is uses the SPSS software program (Statistical Package for Social Sciens) 22.0 for Windows. The results of this research prove that the Percentage of Asset Cash to Profitability (Return On Assets), Liquidity (Current Ratio) has a significant effect on Profitability (Return On Asset), Cash Turnover and Liquidity (Current Ratio) there is a significant and significant influence on Profitability (Return On Asset) for Pharmaceutical Companies Registered on the Indonesia Stock Exchange for the period 2012-2016.